Peningkatan Keterampilan Bermain dan Kerja Sama Tim pada Anak Sekolah Dasar dalam Permainan Mini Voli Melalui Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) - Shintia Nur Fadillah; Suherman Slamet; Eva Sri Gumilang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) cooperative learning model on the playing skills and teamwork of elementary school students in mini volleyball games. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group pretest-posttest design. The research sample consisted of 70 fifth-grade elementary school students who were divided into an experimental group and a control group. The research instruments consisted of the Game Performance Assessment Instrument (GPAI) to measure playing skills and a teamwork questionnaire to measure students' teamwork ability. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, and hypothesis testing with the assistance of SPSS. The results showed that the implementation of the Teams Games Tournament (TGT) cooperative learning model had a significant effect on improving students' playing skills (p < 0.001). In addition, students' teamwork also showed a significant improvement after the treatment (p = 0.035). Based on these findings, it can be concluded that the Teams Games Tournament (TGT) cooperative learning model is effective in improving the playing skills and teamwork of elementary school students in mini volleyball learning. Keywords: Mini Volleyball, Teamwork, Playing Skills, Elementary School, Teams Games Tournament